Perancangan Interior Sentra Kuliner dan Jajanan Pasar Khas Jawa Timur di Surabaya - Pratiknjo, Timfanny Meilinda (Intra, 2015)
This design is accomplished to appreciate East Java culinary culture in Surabaya. East Java is a province in the eastern part of Java Island which consists of 9 municipalities and 29 regencies. A large number of municipalities and regencies makes East Java Province hasÂ  so many ethnics, arts, customs and cultures. This diversity is particularly made up in the culinary field. Thus, the design is made to create a commercial space in the culinary field which is able to accomodate the needs of the people of Surabaya with natural, comfortable and fresh shades of interior design.Designing a culinary commercial space in Surabaya needs a unique basic idea to attract people with new things, the idea will be able to change the mindset of the people of Surabaya over the design of traditional restaurants which tends to be too heavy with many custom engravings. Whereas the concept of a regional culture is not only based on customs and traditions alone. In the application, the selected design uses a modern style, but the design will still adjust to the climate and geographical location of Surabaya to create the natural feel. Establishing a culinary center and typical snacks of East Java "Semanggi Food Carte" will provide a distinguished interior atmosphere of the restaurant which is believed to be the icon of the main culinary centre in the city of Surabaya.